Breaking the Silence: Sexual Harassment of Mexican Women Farmworkers. Issue 2 (2nd April 2016) - Kim, Nicole Jung-Eun; Vásquez, Victoria Breckwich; Torres, Elizabeth; Nicola, R. M. Bud; Karr, Catherine
ABSTRACT: The purpose of this study was to understand Mexican women farmworkers' perceptions of workplace sexual harassment, its related factors and consequences, and potential points of intervention. This community-based participatory research study conducted focus groups with 20 women farmworkers in rural Washington. Four coders analyzed and gleaned interpretations from verbatim transcripts. Three main themes were identified. It was learned that women farmworkers: (1) frequently experienced both quid pro quo and hostile work environment forms of sexual harassment; (2) faced employment and health consequences due to the harassment; and (3) felt that both individual- and industry-level changes could prevent the harassment. Based on these findings, the authors identified three sets of risk factors contributing to workplace sexual harassment and recommend using a multilevel approach to prevent future harassment in the agriculture industry.